This is not a copy writing at the iterative turn - Marczewska, Kaja (Bloomsbury Academic, 2018)
"In This Is Not a Copy, Kaja Marczewska identifies a characteristic 'copy-paste' tendency in contemporary culture--a shift in attitude that allows reproduction and plagiarizing to become a norm in cultural production. This inclination can be observed in literature and non-literary forms of writing at an unprecedented level, as experiments with text redefine the nature of creativity. Responding to these transformations, Marczewska argues that we must radically rethink our conceptions of artistic practice and proposes a move away from the familiar categories of copying and originality, creativity and plagiarism in favour of the notion of iteration. Developing the new concept of the Iterative Turn, This Is Not a Copy identifies and theorizes the turn toward ubiquitous iteration as a condition of text-based creative practices as they emerge in response to contemporary technologies. Conceiving of writing as iterative invites us to address a set of new, critical questions about contemporary culture. Combining discussion of literature, experimental and electronic writing, mainstream and independent publishing with debates in 20th- and 21st-century art, contemporary media culture, transforming technologies and copyright laws, This Is Not a Copy offers a timely and urgently needed argument, introducing a unique new perspective on practices that permeate our contemporary culture."--Bloomsbury Publishing
Includes bibliographical references and index
Keywords: Copying; Plagiarism; Originality in literature; Creative writing; Experimentelle Lyrik; Kopie; Englisch; Nachahmung